Use of benefits during pregnancy: a cohort study in four organisations in Spain - Consol Serra; Fernando G Benavides; Xavier Duran; Pilar Peña; Martina Lupia; Rosa Serrano; Joan Inglés; Júlia Pratdesava; Pere Plana (BMJ Public Health)
Objectives To analyse the use of either sick leave (SL) benefit and/or pregnancy-related occupational risk (POR) benefit by workers taking work absence during pregnancy.Methods Retrospective cohorts of working women from the beginning to the end of pregnancy in three public hospitals and one pharmaceutical company, between 2015 and 2019. We measured the frequency and duration of absences, by age and occupational variables, and cumulative absence days, classifying work status as at work, on SL and on POR absence. Differences between groups for each variable were analysed through the Kruskal-Wallis rank test followed by Dunn’s Pairwise Comparisons. Sequence analysis was used to identify pregnancy trajectories.Results Among 1116 pregnant workers, absence days due to SL ranged from 9.9% to 28.6% of total possible working days, from 9.2% to 38.4% due to POR, while only 3.9% did not take any absence. Nurse aides and nurses used benefits most often and for the longest duration with respect to other occupational categories (p value<0.001). Age had no statistically significant difference (p value=0.245). Three pregnancy trajectories were identified, characterised by mostly active work, active work combined with POR and active work with SL, with differences by workplace, occupation and work area (p value<0.001). The total time in days during which pregnant women were actively working ranged between 56% and 64% depending on the organisation.Conclusions This study in four organisations shows a very similar pattern regarding total time absent from work during pregnancy. Women were actively working for two-thirds of their pregnancy. Of the remaining time, while in two organisations, absences were mainly due to SL, in other two were due to POR. Organisational variations in the management of pregnant women could be an explanation. We need further investigation on this topic.